Impurity-induced Tc reduction in high-temperature superconductors - Matsunaka, Daisuke (Animo Repository, 2004)
We study the effects of nonmagnetic impurities substituted for Cu atoms on the superconducting transition temperature Tc in high-temperature cuprate superconductors, using the d-p model within the fluctuation exchange approximation and the coherent potential approximation. Tc near the optimum-doped region reduces more rapidly than that for the over-doped region. We show that the rapid reduction of Tc is due mainly to the damping of the quasiparticle in our formalism.